The Emergence Of The Science Of Jurisprudence - Ro`zmetov Muhammad Mustafo (Zien Journals, 2024)
The science of jurisprudence is one of the necessary sciences in human life. That is why jurists attached great importance to this science. Of course, this knowledge comes from the age of happiness. At that time, the science of jurisprudence developed in a practical form. In three articles, we will talk about the emergence of jurisprudence
Keywords: Fiqh; jurist; madhhab